Spectator sports and its role in the social marketing of national unity: Insights from a multiracial country. (27th May 2019) - Lim, Weng Marc
Abstract: Spectator sports are a form of leisure that can be leveraged by social marketers to create myriad profound impacts on society. This article aims to examine the role of leisure in the form of spectator sports in the social marketing of national unity. Using sports for development and social marketing as lenses to inform an interpretive case study predicated on a thematic analysis of qualitative secondary sources on spectator sports in multiracial Malaysia, this article finds that leisure in the form of spectator sports can act as an entry point to, a promoter of, an educator of, a symbol of, an initiator of conversations and dialogs on, and a unifying mechanism for national unity. Specifically, these roles enacted by spectator sports contribute to uniting multiracial communities within and beyond a sporting cause, or inside and outside spectator sports, in which inherent differences are cast aside and commonalities are embraced.